Examine on Use of Information Seeking Behaviour: Examining the Use of Information Resources in Medical College Libraries of Madhya Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The paper aims to examine the use of information resources in the medical college libraries of Madhya Pradesh related to allopathic medicine. It also describes brief overview of Medical Science Education in India with special reference to Madhya Pradesh College Libraries. Information is viewed as the fifth essential need of each human being notwithstanding air, water, food and safe house. In all social statuses it has become a significant fixing. Information is a crude material for a correct basic leadership from individual to legislative level. It is a significant element for the financial and sound advancement of a country.